The Magnitude of Job Satisfaction among Healthcare Providers in Qassim, Saudi Arabia - Alrebish, Saleh A. (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: Healthcare personnel job satisfaction is an important aspect of healthcare management since it has been demonstrated to be closely related to greater patient adherence to treatments, a higher quality of care, and higher patient satisfaction. The present study assessed the job satisfaction level among healthcare providers in Qassim, Saudi Arabia. Materials and Methods: The present study employed a cross-sectional research methodology, which was carried out during September and October of the year 2023. Results: The survey was completed by a total of 292 professionals working in the field of healthcare. The most important factors that affect the job satisfaction of healthcare providers are “having the ability to do things that align with my conscience” (75.34%) and “Communication between coworkers” (71.58%). About 35% of the respondents had a high satisfaction level and 18.83% of them had moderate satisfaction. Conclusion: The present study found a poor level of satisfaction among healthcare personnel in Qassim. Healthcare firms should investigate the requested steps to be implemented to reduce workplace dissatisfaction and boost employee gratification.